Constative study on the improvement of technique in high school students through means specific to the game of football - Tatarcan Cătălin-Andrei (Editura Univeristatii "Stefan cel Mare" din Suceava, 2023)
Studies on the importance of applying football exercises to middle school students show that these exercises bring numerous benefits both physically, mentally and socially. Developing technical skills by practicing the exercises specific to the game of football is a sport that involves a wide range of technical skills such as ball control, dribbling, passing and shooting. By applying soccer-specific exercises, players in the school representative team can improve their technical skills and reach a higher level of performance in these aspects. The article aims to improve the general but also specific technical execution of hitting and passing the ball through exercises specific to current football. The study was carried out in the "Mitocu Dragomirnei" Secondary School, where boys from the 6th and 7th grades were used. The experiment was carried out over a period of one year.